RNA-seq based transcriptome analysis of murine macrophages RAW264.7 treated with multi-herbal extracts reveals immunomodulatory potential and mechanism. Issue 1 (31st December 2023) - Jin, Meng-Yuan; Chen, Xin; Wu, Qin; Guo, Zhi-Jian; Zhang, Rui; Jiang, Yi-Fan; Li, Xiang; Zhang, Li-da; Wang, Yu-Liang; Zhou, Xuan-Wei
ABSTRACT: Shenling Baizhu Powder is a traditional Chinese medicine formula that has been used for thousands of years to invigorate spleen, nourish stomach and regulate immune function. The multi-herbal extracts, an improved formular from Shenling Baizhu Powder, were used in our study to investigate its immune-enhancing effects and underling mechanisms. Based on UPLC-Q-TOF-MS and SPME-GC-MS analysis, 106 chemical compounds were identified from the extracts. In vitro assays indicated that the extracts could promote cell proliferation and NO secretion of RAW264.7 cells. RNA-seq and RT-qPCR showed that RAW264.7 cells treated with extracts increased the expression of pro-inflammatory factors IL-1β, iNOS, TNF-α, and TGF-β. Western-Blot revealed that the extracts could significantly enhance ERK phosphorylation level, and slightly increased JNK and p38 phosphorylation levels. These data suggest that multi-herbal extracts have a potential of regulating immune response via the JNK/p38/ERK signalling of MAPK pathways in RAW264.7 cells. GRAPHICAL ABSTRACT: UF0001